Dynamic [99mTc]Tc-mebrofenin SPECT/CT in preoperative planning of liver resection: a prospective study - Annamária Bakos; László Libor; Szabolcs Urbán; Tibor Géczi; Mátyás Bukva; József Hőhn; György Lázár; András Nagy; István Farkas; Gábor Sipka; László Pávics; Zsuzsanna Besenyi (Scientific Reports, 2024)
Abstract Background At least 20% of the future liver remnant must function properly after liver tumor resection to avoid post-hepatectomy liver failure (PHLF). [99mTc]Tc-mebrofenin scintigraphy and SPECT are unique noninvasive, quantitative methods for evaluating liver function via hepatocellular bilirubin clearance. Aim To evaluate the value of dynamic [99mTc]Tc-mebrofenin SPECT/CT parameters for predicting clinically relevant PHLF according to the ISGLS criteria. Methods Thirty-five patients underwent dynamic [99mTc]Tc-mebrofenin SPECT/CT imaging to determine the FLR volumetric rate, functional volume rate, total liver filtration and FLR filtration. On the same day, two-dimensional ultrasound shear wave elastography (2D-SWE) was used to assess parenchymal fibrosis in the FLR. The quantitative dynamic SPECT parameters were compared with the relevant clinical scores and ICG. Results The total liver filtration was inversely correlated with the ICG-R15 and MELD-Na score. Twenty-four patients underwent major liver resection due to an adequate FLR rate and did not die within 90 days after the procedure. ROC analysis revealed that the FLR filtration was a significant predictor of PHLF. The best cutoff value for FLR filtration was 2.72%/min/m2. Conclusion Dynamic [99mTc]Tc-mebrofenin SPECT/CT is an essential tool for selecting patients at risk of clinically relevant PHLF after liver resection.